“Restitución De Lo Sustraído Por Parte De Los Funcionarios Públicos Que Han Incurrido En Delitos Contra La Eficiencia De La Administración Pública. - Aguilar Balcázar, Gisella Mishel (2021)
The present research job whose subject is "RESTITUTION OF WHAT IS SUBSIDIZED BY PUBLIC OFFICIALS WHO HAVE INCURRED IN CRIMES AGAINST THE EFFICIENCY OF THE PUBLIC ADMINISTRATION" aims to demand that public officials the restitution of what was stolen when they have committed crimes against the efficiency of the Public Administration typified in the third section, fifth chapter of the second book of the Comprehensive Organic Criminal Code and establish in the law the reparation of the damages caused by the offender in its entirety. One of the great problems of the embezzlement of public funds towards the personal interests of those who carry out these deplorable acts is the obstruction in the collective progress of Ecuadorian society, due to the fact that all these stolen assets are not reflected or made effective in the different needs that it has to cover the Ecuadorian State, evident in the great deficiencies within the fields of education, health, communication, among others; those that fail to meet the expectations of the Ecuadorian people. The existence of an exemplary sanctioning mechanism is necessary, which requires both a judicial system that is capable of identifying and adequately sanctioning corrupt behaviors, as well as adequate public dissemination of said 6 behaviors, so that in the latter case society can carry out the attribution of responsibilities that correspond to it. The response capacity of the judiciary to this type of crime is highly inefficient both in the investigation and prosecution of the same and in the application of sanctions. In this sense, the low effectiveness of justice in the prosecution of these crimes is reflected in few sentences, several prescriptions due to lack of momentum in the cases, lack of elevations to oral proceedings and excessive delays in the processing of cases. Being essential to eradicate these behaviors in order to obtain an effective restoration of the damages caused to the State. In the development of this research work, for the verification of all the aforementioned, the scientific method was used, which has been the most appropriate instrument that allows to reach knowledge, development, execution and give possible solutions to the problem raised, through reflection comprehensive and direct contact with objective reality; through required logical processes, that is why in this research some methods and techniques of the scientific method are used, such as the inductive, deductive, descriptive method, observation, analysis and synthesis, observing in general, the great dissatisfaction of the population with the work of the judicial function regarding the prosecution of these crimes that affect an entire country. 7 It is for all this that this investigative work is of great relevance, in order to reform the Comprehensive Organic Criminal Code in relation to Crimes against the Efficiency of the Public Administration and thus reduce this entire wave of corruption that has been stalking the country since unmemorable times.